Review on controller design in pneumatic actuator drive system - Syamiza Jamian; S. N. S. Salim; M. N. Kamarudin; M. Zainon; M. S. Syed Mohamed; L. Abdullah; M. A. M. Hanafiah (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
A pneumatic actuator is a device that converts compressed air into mechanical energy to perform varieties of work. It exhibits high nonlinearities due to high friction forces, compressibility of air and dead band of the spool movement which is difficult to manage and requires an appropriate controller for better performance. The purpose of this study is to review the controller design of pneumatic actuator recommended by previous researchers from the past years. Initially, the basic views of the pneumatic will be presented in terms of introduction to the pneumatic actuator and its applications in industries. At the end of this review, discussions on the design of the controllers will be concluded and further research will be proposed along with the improvement of control strategies in the pneumatic actuator systems.